(untitled) (Journal of Information Technology and Digital World, 2020)
In the modern world, software plays an integral role, following an effective methodology while developing these software have become crucial to accomplish the project goal. Agile approach is a methodology which have been introduced as an effective approach for developing software to increase productivity and efficacy of software development process compare to traditional methodologies. The rapid deployment of solutions, early and continuous delivery of valuable product to the customers, resource utilization, rapid issue detection, customer focus, effective collaboration and communication, adapting changes and flexibility are the key principles of Agile. Meeting the deliverables of the project without compromising its scope, quality and timeline within a limited budget is a key to success. Use of effective project management methodology and identification of critical success factors to achieve project success is essential to understand for any organization whether it is software or non-software.